2007
DOI: 10.1111/j.1095-8312.2007.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual, seasonal, and environmental variation in plasma carotenoids in great tits, Parus major

Abstract: In many birds, carotenoids have dual functions as irreversible plumage pigments and as physiologically essential vitamins and antioxidants. They must be obtained through the diet and may therefore be a limiting resource, a constraint that is likely to vary with factors such as sex, habitat, and time of year. In the present study, we investigated signs of carotenoid limitation in great tits, Parus major, in relation to sex, season, year, and within an urban versus a rural habitat. The two main carotenoids, lute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Both of these resources undergo significant annual and seasonal oscillations in abundance (Herrera et al, 1998;Jones et al, 2003) that may explain our results. Both the effects of year and season have been already reported in the case of the Great Tit Parus major, the only species in which seasonal and annual variation in plasma carotenoids has been studied to date (Isaksson et al, 2007). Our results confirm that these factors are applicable to the passerine communities present in our study area.…”
Section: Discussionsupporting
confidence: 88%
“…Both of these resources undergo significant annual and seasonal oscillations in abundance (Herrera et al, 1998;Jones et al, 2003) that may explain our results. Both the effects of year and season have been already reported in the case of the Great Tit Parus major, the only species in which seasonal and annual variation in plasma carotenoids has been studied to date (Isaksson et al, 2007). Our results confirm that these factors are applicable to the passerine communities present in our study area.…”
Section: Discussionsupporting
confidence: 88%
“…First, the marginal increase in ROM concentration might be explained by an inappropriately high dose of supplementary antioxidant (Hill and McGraw, 2006;Hill and Johnson, 2012). We can reject this hypothesis because blood assays revealed that total carotenoid concentration in the plasma of supplemented birds was within the natural range and lower than previously reported in the same and/or closely related species during the breeding period (Hõrak et al, 2004;Biard et al, 2005;Isaksson et al, 2007a) and in autumn (Isaksson et al, 2007a). Another possibility could be that increased availability of carotenoids in the diet might promote short-term benefits for the antioxidant system through decreased ROM concentration (Larcombe et al, 2008) but might also induce a long-term effect on ROM concentration by lowering the stimulation of antioxidant capacity (Metcalfe and Alonso-Alvarez, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…In order to investigate the role of carotenoids in regulating oxidative stress, we manipulated carotenoid availability through dietary supplementation and measured plasma total antioxidant capacity, ROM concentration as a measure of potential oxidative damage, and concentrations of plasma carotenoids, vitamin A and vitamin E. To be able to examine the effect of carotenoids on oxidative stress, our study was conducted after moult because at this time there are few available carotenoids as a consequence of low insect abundance (Sehhatisabet et al, 2008;Vel'ky et al, 2011), and any stored pigments should have been used for producing yellow feather coloration. Previous studies in species with carotenoid-based plumage colour showed that plasma carotenoid concentration was lower in winter (after moult) than before or during moult, which could be due to lower carotenoid availability and/or to depletion of carotenoid stores during feather growth (Isaksson et al, 2007a;Del Val et al, 2013). Moreover, birds cannot remobilize carotenoids that have already been deposited in feathers, unlike those used for bill or soft tissue coloration (Hill and McGraw, 2006).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The most recent carotenoid studies use this technique, which offers powerful carotenoid quantification and identification of unknown compounds in a mixed sample. Much of the information on the carotenoids of bird plumage, fish meat and vegetables has been obtained using very similar HPLC protocols and chemical extraction techniques (Minguez-Mosquera and Hornero-Mendez 1993, Moren and Hamre 2002, Isaksson et al 2007, Juola et al 2008). Most use reverse-phase C18 columns and acetonitrile or methanol for mobile phase separation.…”
Section: Methods Of Carotenoid Analysismentioning
confidence: 99%